Pengaruh Spiritual Emotional Freedom Technique (Seft) Dalam Menurunkan Kesepian Pada Warga Binaan Lapas Narkotika Kelas IIA, Kabupaten Gowa - Ahmad Fauzan; Lukman Lukman; Ahmad Ridfah (JBKPI: Jurnal Bimbingan dan Konseling Pendidikan Islam, 2023)
ABSTRACT  The separation of each prisoner from his family, the loss of work and environmental conditions as well as new forms of activity make prisoners vulnerable to loneliness. The purpose of this study was to determine the provision of Spiritual Emotional Freedom Technique (SEFT) therapy in reducing loneliness in prisoners. This study uses a quantitative experimental method with a randomized control group pretest-posttest design. The subjects in this study were 14 prisoners who were divided into 2 groups, the treatment group (mean = 10.93) and the control group (mena = 4.07). The results showed p = 0.002 (p 0.05) for differences in the level of loneliness between groups, the significance value of p = 0.018 (p 0.05) for comparison of pretest (mean = 28.00) and posttest (mean = 20) values. .14) experimental group and p value = 0.18 (p0.05) for the comparison of pretest (mean = 27.87) and posttest (mean = 27.42) in the control group. Based on the results, it was found that there were differences in the effect of giving SEFT in reducing loneliness. Other variables that can affect loneliness are suggested to be controlled more tightly or can be studied in depth in further research, such as personality, psychological conditions and prison environment.